HIV/AIDS narratives: representing Indonesian women in the online information landscape - Alifia Firliani (Faculty of Communications Science, Dr. Soetomo University, 2024)
HIV/AIDS cases among women make up more than 30 percent of national incidence every year in Indonesia. Women are disproportionately susceptible due to gender inequality. Access to online information can improve awareness and equip women to identify their risks as a basis to seek medical testing or for those living with the virus to access support and treatment. This study aims to understand the online information landscape about HIV/AIDS in relation to women in Indonesia. Using thematic analysis across 149 online articles, we found the following themes: prevalence (39), symptoms (37), vulnerability (31), awareness programs (20), information about antiretroviral drugs (12) and HIV testing (10), which illustrates a comprehensive coverage of key aspects related to HIV/AIDS among women in Indonesia within online discourse. They highlight a significant focus on epidemiological data, symptomatology, and the specific vulnerabilities women face in contracting and managing HIV/AIDS and efforts to educate the public and promote prevention strategies. Future research should explore how these themes interact with each other and how they influence public perception and healthcare-seeking behaviour among women affected by HIV/AIDS in Indonesia.